Modelling the Impact of Student Resilience on Attrition Risk in Higher Education: A Structural Equation Modelling - Ubaid Al Faruq; Aden Aden; dameis Surya Anggara; Heri Haerudin; Muhammad Fajar Mediyawan Gintings; Ersam Mahendrawan; Putut Said Permana (AL-ISHLAH: Jurnal Pendidikan, 2026)
Resilience is a factor that affects student attrition in higher education. The objectives of the study were (1) to describe the resilience profile of Universitas Pamulang (Unpam) students and (2) to obtain the results of the level of influence of student resilience on the potential for study dropout at Unpam. The research method used is a quantitative method using a structural equation modelling (SEM) approach. The research population was Unpam students who indicated dropping out of study with 387 respondents. The results obtained the data shows that 70% of respondents are employed, which illustrates economic stability as a factor supporting resilience. Income level also correlates positively with resilience, with higher-income groups scoring higher on resilience. The resilience profile based on seven dimensions shows optimism, emotional regulation, and impulse control as the highest aspects, while causal analysis and empathy are relatively weak aspects. The influence of resilience for causal analysis indicators, empathy has a positive effect on drop-outs, opt-outs, stop-outs, and transfer-outs. Indicators of emotional regulation, optimism, and reaching out negatively affect drop-outs, opt-outs, stop-outs, and transfer-outs. Indicators of self-efficacy have a positive effect on drop-outs and stop outs and a negative effect on opt-outs and transfer-outs. These findings suggest that higher education institutions should prioritize psychological interventions focused on strengthening causal analysis and empathy through counseling and peer-mentoring programs. Furthermore, the significant role of economic stability implies a need for flexible academic policies and financial support systems tailored for working students to effectively mitigate the risk of attrition.